FARMERS RESPONSES TO THE UNINTENDED CONSEQUENCES OF OPEN GRAZING AND UNREGULATED ACCESS TO FARMLANDS ON AGRICULTURAL PRODUCTIVITY AND SUSTAINABILITY IN LOKOJA, KOGI STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
Open grazing is a practice by herdsmen whereby they wander about with their cattle of cows and herds of sheep in fields, bushes and in recent times, in farmlands in search of grasses. Whereas undue access to land by heavy duty trucks in the name of illegal quarrying or supply of building materials have caused more wreckages to the farmlands. The materials used to execute this study include a well-structured questionnaire in which 120 were distributed to farmers and stakeholders around the farming communities in Lokoja. The processing of the acquired data was carried out to check for sampling adequacy with Principal Component Analysis (PCA). The Likert scale method was used to analyze the responses to the various questions in the questionnaires. The result established that; Movement of heavy duty trucks and cattle trampling make tillage of the soil for irrigation farming very difficult. It is recommended that the stakeholders strive hard to protect the farmlands from unnecessary access by herders and trucks that enter for quarrying activities. More so, ranching should be legislated in order to have sustainable production of food.
Keywords: Open grazing; Cattle trampling; Farmlands; Heavy duty-trucks; Sustainable agriculture